2016
DOI: 10.3892/mco.2016.1055
|View full text |Cite
|
Sign up to set email alerts
|

Novel predictive biomarkers for cervical cancer prognosis

Abstract: Abstract. High hypoxic, glycolytic and acidosis metabolisms characterize cervical cancer tumors and have been described to be involved in chemoradioresistance mechanisms. Based on these observations, the present study assessed four selected novel biomarkers on the prognosis of locally advanced cervical carcinoma. A total of 66 patients with stage IIB/IIIB cervical cancer were retrospectively included. The protein expression levels of glucose transporter 1 (GLUT1), carbonic anhydrase 9 (CAIX) and hexokinase 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
2
15
0
1
Order By: Relevance
“…A survival benefit of 12% was previously reported with the combination of chemotherapy + radiotherapy in CC patients [20]. The present findings clearly confirm that patients with locally advanced CC should undergo concomitant chemoradiation, in accordance with international guidelines.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…A survival benefit of 12% was previously reported with the combination of chemotherapy + radiotherapy in CC patients [20]. The present findings clearly confirm that patients with locally advanced CC should undergo concomitant chemoradiation, in accordance with international guidelines.…”
Section: Discussionsupporting
confidence: 90%
“…However in our set of patients, no significant correlation was identified between hemoglobin level and Karnofsky index, suggesting that the poor prognosis value of anemia could not only been seen through the prism of the performance status. Furthermore, previous experimental and clinical studies suggested a direct association between anemia and a poor tumor oxygenation [20], limiting the radio-induced oxygen effect and therefore decreasing the efficacy of radiotherapy. In squamous cell carcinoma and especially in CC, the prognostic impact of anemia is well-established [3, 7, 20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This overexpression is assumed to provide the increased need of glucose for aerobic glycolysis in cancer cells (Warburg effect), in order to sustain proliferation. Induction of GLUT1 mRNA and protein has been considered as an early event in cervical neoplasia as well as in other oncogenic virus‐mediated cellular transformation . In head and neck carcinoma, human papillomavirus (HPV)‐positive cancers display a higher GLUT1 expression, associated with a lower tumour hypoxia signature .…”
Section: Introductionmentioning
confidence: 99%